(untitled) (Bangladesh Journal of Otorhinolaryngology, 2024)
Objective: For the last 20 years, transcanal endoscopic ear surgery has emerged as a viable, ergonomic, and powerful alternative surgical modality of choice replacing the conventional microscopic approach in many ways. This study compares the functional and anatomical outcomes of endoscopic tympanoplasty with microscopic tympanoplasty using full-thickness tragal cartilage as a graft of choice. Methodology: This observational, analytical, retrospective study was conducted in the department of Otolaryngology in a tertiary care hospital over two years. It included an analysis of medical records of 38 patients (above 10 years of age), who underwent conventional microscopic and transcanal endoscopic tympanoplasty (type I) for dry and small/medium size tympanic perforations. Morphological and functional outcomes were compared in both groups by noting the condition of graft and air-bone gap on follow-up. Result: There were 19 patients each in both groups. The mean pre-and post-operative ABG in each group was comparable and the difference was statistically significant in each group ( P< 0.05). Comparing the mean ABG change between both groups, there was a statistically significant difference noted (P<0.05). The success rate was found to be 89.5% (17 /19) in the endoscopic surgery group and 94.7% (18/19) in the microscopic surgery group. The difference in the anatomical success of both groups was not statistically significant. Conclusion: There was no statistically significant difference between both groups regarding graft take-up rates but functionally hearing outcomes were better in the MES group which was statistically significant. Bangladesh J Otorhinolaryngol 2024; 30(1): 5-14